POLA KONSUMSI DAN ATRIBUT-ATRIBUT BERAS SIGER YANG DIINGINKAN KONSUMEN RUMAH TANGGA DI KECAMATAN NATARKABUPATEN LAMPUNG SELATAN - Tio Wanda Hendaris; Wan Abbas Zakaria; Eka Kasymir (Lampung University, 2013)
The objectives of this research are to find out the consumption patterns of household consumers of ”siger” rice, the attributes which become the considerations on consuming “siger” rice, and the preferred attribute combinations of ”siger” rice. This research was conducted in Natar District, South Lampung Regency as the center of ”siger” rice producers and consumers in Lampung Province. The research was conducted by survey method, with the total samples of 52 ”siger” rice consumers that were drawn randomly from the population. A Quantitative (Conjoint) and qualitative descriptive analyses were employed toanswered the objectives. The results showed that consumption patterns of ”siger” rice could be explained as follows. The household of ”siger” rice consumers consumed “siger” rice for 1-5 times/week. They obtained the raw materials from their fields and processed it by themselves. However, they consumed it less than 1 kg/week by mixing it with regular rice, and consumed it because of their own habit. The attributes that became their considerations, from the most to the least important were color, texture, smell, price, and packaging. The preferred attribute combinations of ”siger” rice was cheap price (less than or equal to Rp7,000/kg), dark brown color, chewy, not strong aroma, and unpacked. Keywords: attributes, consumption patterns, consumers, ”siger” rice